Molecular characterization of neoplastic and normal "sister" lymphoblastoid B-cell lines from chronic lymphocytic leukemia. Issue 8 (August 2013) - Lanemo Myhrinder, Anna; Hellqvist, Eva; Bergh, Ann-Charlotte; Jansson, Mattias; Nilsson, Kenneth; Hultman, Per; Jonasson, Jon; Buhl, Anne Mette; Bredo Pedersen, Lone; Jurlander, Jesper; Klein, Eva; Weit, Nicole; et al.
Abstract Chronic lymphocytic leukemia (CLL) B-cells resemble self-renewing CD5 + B-cells carrying auto/xeno-antigen-reactive B-cell receptors (BCRs) and multiple innate pattern-recognition receptors, such as Toll-like receptors and scavenger receptors. Integration of signals from BCRs with multiple surface membrane receptors determines whether the cells will be proliferating, anergic or apoptotic. To better understand the role of antigen in leukemogenesis, CLL cell lines producing monoclonal antibodies (mAbs) will facilitate structural analysis of antigens and supply DNA for genetic studies. We present here a comprehensive genotypic and phenotypic characterization of available CLL and normal B-cell-derived lymphoblastoid cell lines (LCLs) from the same individuals (n = 17). Authenticity and verification studies of CLL-patient origin were done by IGHV sequencing, fluorescence in situ hybridization (FISH) and DNA/short tandem repeat (STR) fingerprinting. Innate B-cell features, i.e. natural Ab production and CD5 receptors, were present in most CLL cell lines, but in none of the normal LCLs. This panel of immortalized CLL-derived cell lines is a valuable reference representing a renewable source of authentic Abs and DNA.